2010
DOI: 10.1088/1751-8113/43/13/135302
|View full text |Cite
|
Sign up to set email alerts
|

Mutually orthogonal Latin squares from the inner products of vectors in mutually unbiased bases

Abstract: Mutually unbiased bases (MUBs) are important in quantum information theory. While constructions of complete sets of d + 1 MUBs in C d are known when d is a prime power, it is unknown if such complete sets exist in non-prime power dimensions. It has been conjectured that complete sets of MUBs only exist in C d if a maximal set of mutually orthogonal Latin squares (MOLS) of side length d also exists. There are several constructions (Roy and Scott 2007 J. Math. Phys. 48 072110; Paterek, Dakić and Brukner 2009 Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The linear combinations also make use of weights. In [6], the weights from the two constructions were found to have very different structures, in the odd prime case. Further investigation of structure and meaning of these weights is required and is currently being undertaken.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The linear combinations also make use of weights. In [6], the weights from the two constructions were found to have very different structures, in the odd prime case. Further investigation of structure and meaning of these weights is required and is currently being undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…In [6], it is shown that for p an odd prime, the MUBs obtained by Theorems 2.2 and 2.3 can be used to construct complete sets of MOLS. In this paper q − 1 MOLS are constructed from q + 1 MUBs for all odd prime powers q = p n .…”
Section: Constructing Mols From Mubs Via Affine Planesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarities between MUBs and mutually orthogonal Latin squares have been analyzed during the last years [17,22,23,24,25,26,27,28,29,30]. In Refs.…”
Section: Introductionmentioning
confidence: 99%